Nutritional value of torula yeast as an alternative protein feedstuff for hybrid Striped Bass (White Bass × Striped Bass) - Chen, Kequan; Yamamoto, Fernando Y.; de Cruz, Clement R.; Gatlin, Delbert M. (John Wiley & Sons Ltd., 2024)
Objective: Two separate trials were conducted to evaluate the digestibility of a novel alternative ingredient, enhanced torula yeast (TY) Cyberlindnera jadinii, in diets for hybrid Striped Bass (HSB; White Bass Morone chrysops × Striped Bass M. saxatilis) and to evaluate graded inclusion levels of this product when replacing soybean products. Methods: In trial 1, the digestibility of TY was determined by testing a reference diet and a TY diet (reference and TY ingredient at an 80:20 ratio). A total of 90 fish were fed the experimental digestibility diets for 21 days, and fecal samples were collected using the stripping technique. In trial 2, a comparative feeding trial evaluated the replacement of soybean meal by TY on a crude protein basis at 50, 100, 200, and 300 g of TY/kg of experimental diet. A total of 150 HSB (18.6 ± 0.21 g/fish mean + SE) were distributed among fifteen 110-L glass aquaria. Each diet was fed to triplicate groups of fish for 9 weeks. Result: In trial 1, apparent digestibility coefficients for protein, lipid, organic matter, and energy of TY were 0.97, 0.98, 0.75, and 0.75, respectively. The availability of essential amino acids also was generally high, ranging from 0.74 to 0.99. For trial 2, a second-order polynomial regression indicated that the optimal inclusion levels of TY in diets were 102, 112, and 109 g/kg for weight gain, feed efficiency, and protein conversion efficiency, respectively. However, the muscle yield linearly decreased with the graded inclusion levels of TY. Linear increases in intraperitoneal fat, hepatosomatic index, and whole-body lipid were observed as the inclusion of TY increased in the diet. Conclusion: In conclusion, nutrients from TY were well utilized by HSB, and it can replace soybean products without affecting growth performance, with the optimal TY inclusion level being 102–112 g/kg of diet.